People and nature : an introduction to human ecological relations. - Moran, Emilio F. (Primers in anthropology, 2008)
This book provides a lively and thoughtful introduction to ecological anthropology by examining the evolving relations between human communities and nature. * Written by a noted anthropologist, geographer, and environmental scientist. * Reviews the evolution of human interactions with the natural world---drawing from anthropology and geography. * Explores those aspects of human ecological relations that seem to account for the greater connectedness of certain societies to their physical environment. * Offers a vision for improved relations between humans and nature -- Présentation de l'éditeur.